A new section in Salix (Salicaceae), S. sect. Baileyanae - Zhan, Zhenfeng; Zhang, Zhixiang; Wang, Lei; Guo, Shaoyu; Luo, Yike (Phytotaxa, 2026)
A new section, Salix sect. Baileyanae is described. The new section containing only one species, S. baileyi, is closely related to S. sect. Daphnella, S. sect. Hukaoanae, and S. sect. Subviminales phylogenetically. However, S. baileyi exhibits significant differences in its morphology and its area of distribution is geographically isolated. There are some morphological similarities of S. baileyi to species of the S. sect. Helix, but they can be easily distinguished by the pronounced differences in morphology of pistillate flowers. S. baileyi is sporadically distributed in south-central China. A detailed comparison of the morphological differences between S. sect. Baileyanae and S. sect. Daphnella, S. sect. Hukaoanae, S. sect. Subviminales, and S. sect. Helix and high-resolution plates of S. baileyi are provided.